Finite mathematics./Margraret L. Lial - Lial, Margaret L.; Greenwell, Raymond N.; Ritchey, Nathan P. (Boston : Pearson/Addison-Wesley, 2008)
Key Message: Lial, Greenwell, and Ritchey continue their tradition of integrating relevant, realistic applications with current data sources to provide an application-oriented text for students majoring in business, management, economics, or the life or social sciences. The many opportunities for technology use allow for increased visualization and a better understanding of difficult concepts. In addition to MyMathLab(R), a complete online course solution, a comprehensive series of video lectures is available for this text. Key Topics: Algebra Reference, Linear Functions (shares with CWA, Brief, and Combo), Systems of Linear Equations and Matrices, Linear Programming: The Graphical Method, Linear Programming: The Simplex Method, Mathematics of Finance, Logic, Sets and Probability, Counting Principles: Further Probability Topics, Statistics, Markov Chains, Game Theory Market: For all readers interested in Finite Mathematics.
Chapter 5 Review 256 Extended Application: Time, Money, and Polynomials 264 Logic 266 6.1 Statements 267 6.2 Truth Tables and Equivalent Statements 276 6.3 The Conditional and Circuits 286 6.4 More on the Conditional 298 6.5 Analyzing Arguments and Proofs 307 6.6: Analyzing Arguments with Quantifiers 319 Chapter 6 Review 329 Extended Application: Logic Puzzles 337 Sets and Probability 341 7.1 Sets 342 7.2 Applications of Venn Diagrams 353 "7.3 Introduction to Probability 365 7.4 Basic Concepts of Probability 376 7.5 Conditional Probability; Independent Events 390 7.6 Bayes' Theorem 409 Chapter 7 Review 418 Extended Application: Medical Diagnosis 429
Includes bibliographical references and index.
Keywords: EMBA; Mathematics